Tradisi Tari Lengger Sebagai Mediasi Penanaman Nilai Gotong Royong di Desa Cangkring, Kabupaten Kebumen (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the implementation of the Lengger Dance tradition and the process of instilling the moral value of mutual cooperation among the younger generation in Cangkring Village, Sadang District, Kebumen Regency. The study used a qualitative approach with ethnographic methods. Data were collected through in-depth interviews, participant observation, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that the Lengger Dance tradition, which has developed since the 1980s, functions not only as a traditional art but also as a space for non-formal moral education for the community. Based on Thomas Lickona's character education framework which includes moral knowing, moral feeling, and moral action, the value of mutual cooperation is instilled through the division of interdependent roles, the implementation of collective rituals, and intensive social interactions during the preparation and performance process. The younger generation who are actively involved in this tradition show a higher level of participation in various social activities. The research findings confirm that traditional arts have a strategic role as a medium for moral education based on local wisdom that is relevant to strengthening the mutual cooperation character of the younger generation